Otitis media and interna with or without polyps in cats: association between meningeal enhancement on postcontrast MRI, cerebrospinal fluid abnormalities, and clinician treatment choice and outcome. Issue 12 (December 2022) - Dutil, Guillaume F; Guevar, Julien; Schweizer, Daniela; Roosje, Petra; Kajin, Filip; Volk, Holger A; Grapes, Nick J; De Decker, Steven; Gutierrez-Quintana, Rodrigo; Abouzeid, Jad; Freeman, Paul; Faller, Kiterie ME; et al.
Objectives: The aim of this study was to evaluate the association between meningeal enhancement (MgE) and cerebrospinal fluid (CSF) analysis results, their individual association with bacteriology results from affected ear samples and whether these test results influenced clinicians' therapeutic choice in cats with otitis media and interna (OMI). Methods: This was a multicentre retrospective study carried out over an 8-year period. Cats diagnosed with OMI, with or without a nasopharyngeal polyp, leading to peripheral vestibular signs were included. Only cats for which MRI with postcontrast T1-weighted sequences and CSF analyses available were included. Cats with intra-axial MRI lesions or empyema were excluded. Results: Fifty-eight cats met the inclusion criteria. MgE was reported in 26/58 cases, of which nine had an abnormal CSF result (increased total nucleated cell count [TNCC] or total protein); 32/58 cases had no MgE, of which 10 showed abnormal CSF results. There was no association between bacteriology results (external ear canal or bulla) and MgE or abnormal CSF results. CSF abnormalities were statistically significantly more common in acute cases (n = 16/37) than in chronic cases (n = 3/21; Fischer's test P = 0.04). Prednisolone was prescribed in 10/16 cases with increased TNCC. Among the 42 cases with normal TNCC, 15 received prednisolone and 13 received non-steroidal anti-inflammatory drugs. Various antimicrobial drugs were prescribed in 53/58 cats. Duration of antimicrobial treatment was similar, regardless of positive bacterial culture (5.58 vs 4.22 weeks), abnormal CSF (5.83 vs 4.76 weeks) or MgE (5.33 vs 4.90 weeks). Conclusions and relevance: No association was found between the CSF and MgE results. Furthermore, no association was found between MgE, CSF or bacteriology findings. In addition, abnormal CSF results might lead the clinician to treat with corticosteroids, but they did not have any impact on duration of antimicrobial treatment. CSF abnormalities were seen significantly less frequently in chronic cases. The outcome tended to be poorer when MgE was detected on MRI.